2016
DOI: 10.5296/emsd.v5i1.8775
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton from Vam Co River in Southern Vietnam

Abstract: <p class="emsd"><span lang="EN-GB">In this study we investigated the variation of phytoplankton and the water quality in Vam Co River, Southern Vietnam. Phytoplankton were bi-monthly monitored in 2011 at 12 sampling sites in the river. Some basic environmental parameters were also monitored including temperature, pH, turbidity, inorganic nitrogen and dissolved phosphorus. The phytoplankton biodiversity and Diatomeae indices were applied for environmental quality evaluation. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The average temperature of the main water bodies in Vinh Long province ranged from 28.5 to 29.9°C which was similar to the water temperature of some other water bodies in Southern Vietnam. This temperature offered favorable conditions for the development of phytoplankton (Dao & Bui, 2016). The environmental parameters of such as pH, dissolved oxygen, nitrate, phosphate were investigated and compared to the National technical regulation on surface water quality QCVN 08:2015/BTNMT.…”
Section: Discussionmentioning
confidence: 99%
“…The average temperature of the main water bodies in Vinh Long province ranged from 28.5 to 29.9°C which was similar to the water temperature of some other water bodies in Southern Vietnam. This temperature offered favorable conditions for the development of phytoplankton (Dao & Bui, 2016). The environmental parameters of such as pH, dissolved oxygen, nitrate, phosphate were investigated and compared to the National technical regulation on surface water quality QCVN 08:2015/BTNMT.…”
Section: Discussionmentioning
confidence: 99%
“…Duong et al (2013) reported the correlation between phosphorus concentration and abundance of cyanobacteria. Dao and Bui (2016) noted the phytoplankton species richness positively correlated with temperature but negatively correlated with nitrate concentration. The same author showed the biodiversity positively correlated with temperature and species number, but negatively correlated with nitrate and phytoplankton abundance.…”
Section: Relationship Between Phytoplankton and Environmental Parametersmentioning
confidence: 92%
“…7, No. 2 2013; Dao and Bui, 2016). Interestingly, water temperature in Bien Ho and Lak Lakes in central highland ranged between that from the two regions of Vietnam, from 23 -28 º C (Table 1, 2).…”
Section: Environmental Parametersmentioning
confidence: 93%
See 2 more Smart Citations